2017
DOI: 10.3389/fcimb.2017.00223
|View full text |Cite
|
Sign up to set email alerts
|

Cytolethal Distending Toxin Enhances Radiosensitivity in Prostate Cancer Cells by Regulating Autophagy

Abstract: Cytolethal distending toxin (CDT) produced by Campylobacter jejuni contains three subunits: CdtA, CdtB, and CdtC. Among these three toxin subunits, CdtB is the toxic moiety of CDT with DNase I activity, resulting in DNA double-strand breaks (DSB) and, consequently, cell cycle arrest at the G2/M stage and apoptosis. Radiation therapy is an effective modality for the treatment of localized prostate cancer (PCa). However, patients often develop radioresistance. Owing to its particular biochemical properties, we p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
(50 reference statements)
0
17
0
Order By: Relevance
“…PC3-KD cells were treated with simvastatin alone (100 μM), IR alone (2 Gy), or simvastatin combined with IR for 48 h. The treated cells were prepared and stained with 20 μg/ml propidium iodide (Sigma-Aldrich) for 1 h. The stained cells were determined by FACScalibur flow cytometer (Becton-Dickinson, San Jose, CA, United States) and the cell cycle distribution was assessed by using Cell Quest software WinMDI (Verity Software House, Topsham, ME, United States) as described previously ( Lin et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…PC3-KD cells were treated with simvastatin alone (100 μM), IR alone (2 Gy), or simvastatin combined with IR for 48 h. The treated cells were prepared and stained with 20 μg/ml propidium iodide (Sigma-Aldrich) for 1 h. The stained cells were determined by FACScalibur flow cytometer (Becton-Dickinson, San Jose, CA, United States) and the cell cycle distribution was assessed by using Cell Quest software WinMDI (Verity Software House, Topsham, ME, United States) as described previously ( Lin et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…According to previous studies, HMGB1 was revealed to be strongly associated with the occurrence and progression of tumors, and its expression level has been connected with the radiosensitivity of various types of cancers (8)(9)(10)(11), however, the underlying mechanism is unclear. In the present study, the expression level of HMGB1 was detected in both esophageal cancer tissues and cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous reports have demonstrated that mTOR kinase suppresses autophagy and apoptosis ( Wang et al, 2015 ) via interference with Atg protein-related formation of autophagosomes ( Levine and Yuan, 2005 ). The PI3K/Akt/mTOR signaling pathways are key axes involved in anticancer drug-induced autophagy, including PCa treatment ( Kim et al, 2017 ; Lin et al, 2017 ; Yu et al, 2017 ). This largely explains the effectiveness of mTOR inhibitors, such as rapamycin, as anticancer agents.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental and clinical data indicate that the mTOR pathway, and its upstream regulators in the PI3K/PTEN/Akt cascade, are altered in a wide variety of human malignancies ( Ciuffreda et al, 2010 ). PI3K/Akt/mTOR complex-1 (mTORC1) and the androgen receptor are two major drivers of PCa, and the PI3K/Akt/mTOR signaling pathway plays a key role in anticancer drug-mediated regulation of autophagy in human PCa cells ( Wang et al, 2016 ; Kim et al, 2017 ; Lin et al, 2017 ). Previous studies have also revealed that the degree of activation of Akt/mTOR signaling components is important, as too little or too much signaling has different consequences depending on the PCa state ( Farrow et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%